Development Of Interactive Teaching Media to Improve the Creativity of UHKBPNP Physics Education Students - Fine Eirene Siahaan; Aprido Bernando Simamora (CV. Pusdikra Mitra Jaya, 2023)
Interactive media is media that asks students to practice a skill and receive feedback. As previously stated, interactive media is a system for presenting lessons with visuals, sound, and video material, which are presented with controls so that students can not only hear and see images and sound, but also give an active response. Creativity is an ability to create something new, unique, different from before, either in the form of an idea or a real work by combining pre-existing elements. The type of research used is the method of developing interactive learning media. The purpose of this study was to increase the creativity of UHKBNPP physics education students in developing interactive teaching media. The conclusions obtained from the development of interactive teaching media to increase the creativity of UHKPNP physics education students are very high, namely the average percentage is 96%. This is obtained from the average percentage of media experts, namely 83.76%. For the average percentage of material experts is 91.25%. This is very good for students in developing media to increase student creativity.